Neuropilin-2 Is a Newly Identified Target of PAX8 in Thyroid Cells - Lucci, Valeria (PLoS One, 2015)
PAX8 is a transcription factor essential for thyroid gland development, as well as for the maintenance of the thyroid differentiated state in the adult. In particular, PAX8 has been comprehensively shown to regulate genes that are considered markers of thyroid differentiation. However, a better knowledge of genes transcriptionally regulated by PAX8 is desirable to clarify its role in endocrine syndromes and cancer susceptibility. In order to further investigate PAX8 downstream targets, we recently performed a genome-wide expression analysis following PAX8 knockdown in FRTL-5 thyroid cells and Neuropilin-2 was identified as a potential transcriptional target of PAX8. In this study, we determined the role of the transcription factor PAX8 in the regulation of Neuropilin-2 expression. Indeed, in thyroid cells PAX8 directly binds the Neuropilin-2 promoter leading to its transcriptional repression. Interestingly, we observed an inverse correlation between the expression of PAX8 and Neuropilin-2 in thyroid carcinoma tissues and cell lines compared to non-tumor counterparts, suggesting a critical role of PAX8 in regulating Neuropilin-2 expression in vivo. Notably, ectopic overexpression of PAX8 in FB-2 thyroid cancer cells promotes Neuropilin-2 downregulation producing a significant reduction in cell proliferation, migration ability, and invasion activity and reverting the cell phenotype from mesenchymal to a more epithelial one. These findings uncover the novel interplay between PAX8 and Neuropilin-2, which is likely to be important in the pathogenesis of thyroid diseases.